(3GdWQjb GdhGVM GdeSdhc Edi eYQaI JQGLe GdNdaGA hGdedhcs - (3GHf GdaQGJ , eMeO Hf YHO GdQMje Hf Ydj Hf eMeO, fGUQ GdOjf GdMfaj,J (B807 (3g` s
(3ChdgG (B:s
(3Chdg aUd ai PcQ CjGe GdYQH hHYV CNHGQgG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B200 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B159s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B49 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1187 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs